Damage prediction of hot stamped boron steel 22MnB5 with a microscopic motivated ductile fracture criterion: Experiment and simulation. (1st March 2020) - Tang, Bingtao; Wu, Fangxing; Wang, Qingfeng; Liu, Jiyuan; Guo, Ning; Ge, Hailong; Wang, Qiaoling; Liu, Peixing
Highlights: Five material parameters in the new ductile fracture criterion are used to expand the application of the criterion. The hybrid experimental-numerical method is used to obtain the fracture strains in various stress states and implemented to calibrate the parameters of ductile fracture criterion. The constructed ductile fracture surfaces calibrated with fracture strain using DIC calculation and hybrid experimental-numerical method are compared. Abstract: With the increasing demand of the reduction of energy consumption and enhancement of automobile safety, the steels with ultra-high strength are widely utilized in automobile industry. Because of the high achievable strength, hot stamping process can be used to supply promising automobile components. The increasing use of high-strength steels leads to great challenges to model the fracture evolution because of their high strength and low ductility. The paper is concerned with plasticity and ductile fracture modelling of hot stamped boron steel 22MnB5, where martensite phase with high yield strength, work hardening and ductility are present during the quenching process. The Lou's ductile fracture criteria which involve void nucleation, growth and coalescence in metallic materials are theoretically reviewed and extended and implanted using users' subroutine VUMAT in ABAQUS/Explicit. Parameters of the selected fracture criterion are determined using calibration tests with various kinds of specimens. Dogbone-like uniaxial tensile specimens are tested to determine the deformation hardening parameters, and specimens with central hole, in-plane shear specimens and notched specimens, balanced biaxial tensile specimens are tested to identify the fracture behavior in various loading stresses. Digital Image Correlation (DIC) method is applied to monitor the surface pattern and record the strain evolution of the specimen surface during the experiment. Because of fully austenitized microstructure, the Mises isotropic yield function is adopted. The hybrid method is used to obtain the fracture strain in various stress directions and implemented to determine the material parameters of fracture model. The constructed ductile fracture surfaces calibrated with fracture strain using DIC calculation and hybrid method are compared in Lode parameter and triaxiality coordinate as well as the principal stress space, respectively. The comparison reveals that the fracture strain obtained by hybrid method is more reasonable. The determined ductile fracture criterion is applied to forecast the fracture onset for seven kinds of specimens and compared with the experiment data. The comparison indicates the simply extended Lou's criterion of ductile fracture can precisely describe the evolution of ductile fracture from uniaxial tensile to biaxial tensile stress state for hot stamped boron steel 22MnB5.